Pengaruh Organization Based Self-Esteem terhadap Work Engagement - Anggitha Zahra Fabiola; Hendro Prakoso (Bandung Conference Series: Psychology Science, 2022)
Abstract. The purpose of this research to know the influence of organization based self-esteem on work engagement conducted on employees marketing and sales division in PT. PEI. Marketing and sales division is the beginning for comapanies to profit from the sale and cooperate with the internal and external. Research methodology used is causality method with the number of participant is 20 employees of division marketing and sales in PT. PEI. This study using a measuring instrument organization based self-esteem scale from Pierce, and a measuring instrument work engagement is UWES-17 from Schaufeli dan Bakker. This findings of this study are 70% employees having high level organization based self-esteem and 55% employees having high level work engagement. Influence of organization based self-esteem on work engagement 64,5%. Abstrak. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh organization based self-esteem terhadap work engagement yang dilakukan pada karyawan divisi pemasaran dan penjualan di PT. PEI. Divisi pemasaran dan penjualan merupakan awal mula bagi perusahaan untuk mendapatkan keuntungan dari hasil penjualan dan bekerjasama dengan pihak eksternal maupun internal. Metode penelitian yang digunakan adalah metode kausalitas dengan jumlah subjek sebanyak 20 orang karyawan divisi pemasaran dan penjualan di PT. PEI. Penelitian ini menggunakan alat ukur organization based self-esteem scale dari Pierce, dan alat ukur work engagement yaitu UWES-17 dari Schaufeli dan Bakker. Temuan dari penelitian ini yaitu 70% karyawan yang memiliki organization based self-esteem yang tinggi dan 55% karyawan yang memiliki tingkat work engagement yang besar. Pengaruh organization based self-esteem terhadap work engagement 64,5%.